Undergraduate Students' Expectations of EFL Lecturers' Teaching Competencies: A Case Study at IAIN Parepare - Muhammad Firmansyah JN; Magdahalena Tjalla; Arqam Arqam (Universitas Muhammadiyah Barru, 2025)
This research aims to explore the expectations of English Language Education Study Program students at IAIN Parepare regarding the components of learning English as a Foreign Language (EFL). There were ten English Language Education Study Program students were interviewed, spesifically seven of them were the third semester and three others from the fifth semester and the researcher got the saturated data within two months of research. Using a qualitative approach with a case study design, this research examines in-depth students’ expectations of EFL lecturers. The data collection method was conducted through in-depth interviews with students to understand their expectations regarding the English language learning process. Research findings reveal that students have comprehensive expectations for the quality of teaching. They want professional lecturers, who have a deep understanding of the material and can create an interactive and fun learning environment. Learning methods are expected to be creative and practical, including a student-centered approach, discussion, role-play, communicative games, and technology integration. The feedback aspect is of particular concern, with students expecting to receive detailed explanations of mistakes, motivational feedback, and appreciation for their efforts. This research concludes that students want an English learning experience that is interactive, meaningful, and supports holistic competency development. The research findings provide important insights for curriculum development, improving the quality of teaching, and adapting learning strategies that are more aligned with student needs and expectations in today's higher education context.